Consumers Attitude towards Ads on Social Media - Ghimire, Biraj; Dahal, Suman; Thapa, Bharat Singh (Nepalese Journal of Management Science and Research, 2019)
The purpose of the study was to investigate influence of advertisement traits on attitude towards Ads on social media and intention to use them for purchase decision. The study used Structural Equation Modeling (SEM) to examine the relationship. The validity and reliability of the constructs were evaluated using exploratory factor analysis (EFA). The EFA was conducted using Principal Component Analysis and Varimax Rotation Method. 7 factors explained 67% of variation. The result also showed sampling adequacy with Kaiser- Meyer-Olin (KMO) test and Bartlett’s Test of Sphericity indicated that sample of 255 was appropriate for factor analysis. The result provided a justifiable range of construct reliability and discriminant validity. Consequently, structural model was developed. Confirmatory Factor Analysis was conducted to test the goodness of the model. The result indicated that advertisement on social media with informative and entertaining contents were more likely to be used by the consumers. Similarly, favorable attitude towards Ads on social media had a positive intention to use the message for purchase decision.